The Role of Weather Indicators in Energy Consumption - NITU, C.; DOBRESCU, A. S. (Advances in Electrical and Computer Engineering, 2008)
This paper presents a method for predicting the consumption of energy. The prediction is realized for the energy used for heating, where the thermal comfort has an important role. The equations that define the thermal comfort in function of the weather indicators are also mandatory for the research.